Safety and Side Effect Profile of Liposome Bupivacaine (Exparel) in Peripheral Nerve Blocks - Ilfeld, Brian M; Viscusi, Eugene R; Hadzic, Admir; Minkowitz, Harold S; Morren, Michael D; Lookabaugh, Janice; Joshi, Girish P (Regional anesthesia and pain medicine, 2015)
Liposome bupivacaine (Exparel) is a multivesicular liposomal formulation of bupivacaine currently approved in the United States for single-dose administration into the surgical site to provide postsurgical analgesia. This retrospective analysis examined safety data from clinical trials involving the off-label use of this formulation in peripheral nerve blocks. Data from 6 controlled (phases I-III) studies were compiled involving single-injection ankle, femoral nerve, and intercostal nerve blocks (2 each). Adverse events (AEs) were monitored for 1 to 30 days after study drug administration. Of 575 subjects, 335 received liposome bupivacaine (2-310 mg), 33 received bupivacaine HCl (75-125 mg), and 207 received normal saline (placebo). Overall, 76% of subjects receiving liposome bupivacaine experienced 1 or more AEs compared with 61% receiving bupivacaine HCl and 76% receiving placebo. The most frequently reported AEs among subjects receiving liposome bupivacaine were nausea, pyrexia, pruritus, constipation, and vomiting. The most common treatment-related AE was hypesthesia among subjects treated with liposome bupivacaine or bupivacaine HCl. Incidence of nervous system AEs for liposome bupivacaine, bupivacaine HCl, and placebo was 21%, 27%, and 21%, respectively. Similarly, incidence of cardiac AEs was 9%, 0%, and 12%, respectively. At least 1 serious AE occurred in 8% of subjects receiving liposome bupivacaine compared with 10% of those receiving placebo (none assessed by investigators as related to study medication). Liposome bupivacaine has a similar safety and side effect profile to bupivacaine HCl and normal saline, suggesting that most of the more common AEs are related to either opioid rescue or the surgical procedure itself.